Single molecule mechanics of the kinesin neck - Bornschlögl, Thomas (National Academy of Sciences, 2009)
Structural integrity as well as mechanical stability of the parts of a molecular motor are crucial for its function. In this study, we used high-resolution force spectroscopy by atomic force microscopy to investigate the force-dependent opening kinetics of the neck coiled coil of Kinesin-1 from Drosophila melanogaster. We find that even though the overall thermodynamic stability of the neck is low, the average opening force of the coiled coil is >11 pN when stretched with pulling velocities >150 nm/s. These high unzipping forces ensure structural integrity during motor motion. The high mechanical stability is achieved through a very narrow N-terminal unfolding barrier if compared with a conventional leucine zipper. The experimentally mapped mechanical unzipping profile allows direct assignment of distinct mechanical stabilities to the different coiled-coil subunits. The coiled-coil sequence seems to be tuned in an optimal way to ensure both mechanical stability as well as motor regulation through charged residues.